2022
DOI: 10.2113/2022/6058346
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Deformation Structures and Tectonics of the Active Orogenic Fold-Thrust Belt: Insights from the Outer Indo-Burman Ranges

Abstract: The tectonic deformation of the outer Indo-Burman Ranges (i.e., Chittagong Tripura Fold Belt, CTFB) is associated with the oblique convergence of Indo-Burmese plates since the latest Miocene. This article presents detailed field evidence of deformation structures and their kinematics in the exposed Tertiary successions in the CTFB. We combine observations made in this study with the published structural, geodetic, and seismic data sets to present an overview of the active tectonic framework of the region and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…Therefore, the NNE–SSW trending and fold‐related lineaments are lesser in number in the lineament map and rose diagrams (Figure 3). Fortunately, some of our remote sensing‐based mapped structures are in good agreement with some of the structures mapped by integrating remote sensing and field studies of the recent study by Hossain et al (2022). They showed both axial fracture sets (NNW–SSE trends related to fold structures) and oblique/cross‐axial fracture sets (NE–SW and E‐W trends, which are fold‐related conjugate fractures) in only selected anticlines, such as Basin 2 of this study.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Therefore, the NNE–SSW trending and fold‐related lineaments are lesser in number in the lineament map and rose diagrams (Figure 3). Fortunately, some of our remote sensing‐based mapped structures are in good agreement with some of the structures mapped by integrating remote sensing and field studies of the recent study by Hossain et al (2022). They showed both axial fracture sets (NNW–SSE trends related to fold structures) and oblique/cross‐axial fracture sets (NE–SW and E‐W trends, which are fold‐related conjugate fractures) in only selected anticlines, such as Basin 2 of this study.…”
Section: Discussionsupporting
confidence: 86%
“…The well‐known earthquake events include the Chittagong earthquake of 1762 (R 8.5+), the Sirajganj earthquake of 1787 (MM X), the Cachar earthquake of 1869 (R 7.5), the Bengal earthquake of 1885 (M w 6.8), Great Indian/Assam earthquake of 1897 (M w 8.1), Srimangal earthquake of 1918 (M w 7.6), Meghalaya earthquake of 1923 (M w 7.1), Dubri earthquake of 1930 (M w 7.1), Bihar‐Nepal earthquake of 1934 (M w 8.1), Assam earthquake of 1950 (R 8.5), and Nepal earthquake of 2015 (M w 7.8) (Hossain et al, 2019). The recent tectonic activity of the study area was also demonstrated in the recent detailed investigation from field mapping, fold structural analysis, fracture/lineament analysis, and palaeostress and kinematic analysis of faults by Hossain et al (2022). Also, several new lineaments of dominant ENE–WSW to E–W trends with secondary NNE–SSW and WNW–ESE trends were mapped in our study (Figure 3).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations